2018
DOI: 10.1016/j.ejc.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Orbits of plane partitions of exceptional Lie type

Abstract: For each minuscule flag variety X, there is a corresponding minuscule poset, describing its Schubert decomposition. We study an action on plane partitions over such posets, introduced by P. Cameron and D. Fon-der-Flaass (1995). For plane partitions of height at most 2, D. Rush and X. Shi (2013) proved an instance of the cyclic sieving phenomenon, completely describing the orbit structure of this action. They noted their result does not extend to greater heights in general; however, when X is one of the two min… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Observe that the size of this orbit is 4, and that the average of ddeg along this orbit is ) for a minuscule poset P was studied by Rush and Shi [70] and later by Mandel and Pechenik [48] in the context of cyclic sieving, but the results they obtained were somewhat sporadic. We believe rowmotion acting on PP ℓ (P ) behaves better than rowmotion acting on J(P × [ℓ]): for example, below we conjecture a uniform cyclic sieving result for rowmotion acting on PP ℓ (P ) when P is a minuscule poset.…”
Section: · · ·mentioning
confidence: 99%
See 1 more Smart Citation
“…Observe that the size of this orbit is 4, and that the average of ddeg along this orbit is ) for a minuscule poset P was studied by Rush and Shi [70] and later by Mandel and Pechenik [48] in the context of cyclic sieving, but the results they obtained were somewhat sporadic. We believe rowmotion acting on PP ℓ (P ) behaves better than rowmotion acting on J(P × [ℓ]): for example, below we conjecture a uniform cyclic sieving result for rowmotion acting on PP ℓ (P ) when P is a minuscule poset.…”
Section: · · ·mentioning
confidence: 99%
“…For example, for the rectangle poset P = [a] × [b], the order of row acting on PP ℓ (P ) is a + b for all ℓ ≥ 1 (see Theorem 4.20 below); while Cameron and Fon-Der-Flaass [10] showed that row acting on J(P × [2]) has order a + b + 1. Order ideal rowmotion acting on J(P × [ℓ]) for a minuscule poset P was studied by Rush and Shi [70] and later by Mandel and Pechenik [48] in the context of cyclic sieving, but the results they obtained were somewhat sporadic. We believe rowmotion acting on PP ℓ (P ) behaves better than rowmotion acting on J(P × [ℓ]): for example, below we conjecture a uniform cyclic sieving result for rowmotion acting on PP ℓ (P ) when P is a minuscule poset.…”
Section: Remark 419mentioning
confidence: 99%
“…In this section, we recall the definition and classification of minuscule posets. For additional background, see, e.g., [Pro84,Ste94,TY09a,RS13,MP18,HPPW20,Oka21].…”
Section: Minuscule Posetsmentioning
confidence: 99%
“…Unfortunately, our proof of Theorem 1.2 is not type-uniform, but relies on the classification of minuscule posets, with corresponding case-by-case analysis. In the exceptional types, it relies on the author's explicit computer calculations reported in [MP18]. It would be very interesting to have a uniform proof of Theorem 1.2.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing tableaux were perhaps first studied in their own right in [TY09], although they appeared earlier in various contexts (e.g., [EG87,JPS98]). As in [MP18], we say an increasing tableau T is gapless if the set of numbers appearing in T is an initial segment of Z ą0 . We write Inc gl pλq for the set of all gapless increasing tableaux of shape λ.…”
Section: Increasing Tableauxmentioning
confidence: 99%